Bisvinylated [R–Ge9–Ge9–R]4– Cluster Dimers12. Issue 6 (23rd April 2015) - Benda, Christian B.; He, Haiyan; Klein, Wilhelm; Somer, Mehmet; Fässler, Thomas F.
Abstract The syntheses, crystal structures, and NMR and Raman spectroscopic characterization of two compounds with a new member of the organically functionalized dimeric Ge9–Ge9 polyanion [R–Ge9–Ge9–R]4– with R = CH=CH2 are presented. [K([2.2.2]crypt)]4[(CH2=CH)–Ge9–Ge9–(CH=CH2)]·1.76 en (1) was synthesized either at elevated temperature by the reaction of K4Ge9 and bis(trimethylsilyl)acetylene in ethylenediamine or at ambient temperature in the presence of Pt(PPh3)4. [K(18crown‐6)]4[(CH2=CH)–Ge9–Ge9–(CH=CH2)]·4 en (2) was obtained from the prefabricated monomeric bisvinylated Ge9 cluster [Ge9(CH=CH2)2]2– and an ethylenediamine solution of the intermetallic compound K4.79Co0.79Sn9. The reductive cleavage of one or two vinyl groups from [Ge9(CH=CH2)2]2– – a prerequisite for the latter reaction – could be shown by reacting a solution of the divinylated [Ge9(CH=CH2)2]2– anion in liquid ammonia with elemental potassium, which resulted in the formation of the ligand‐free Ge94– cluster in the new compound [K5(OH)]Ge9(NH3)11 (3).